2014
DOI: 10.1002/sim.6256
|View full text |Cite
|
Sign up to set email alerts
|

Disease mapping via negative binomial regression M-quantiles

Abstract: We introduce a semi-parametric approach to ecological regression for disease mapping, based on modelling the regression M-quantiles of a Negative Binomial variable. The proposed method is robust to outliers in the model covariates, including those due to measurement error, and can account for both spatial heterogeneity and spatial clustering. A simulation experiment based on the well-known Scottish lip cancer data set is used to compare the M-quantile modelling approach and a random effects modelling approach … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…It is shown that the hierarchical median regression via a Poisson log-normal representation (HQRPLN) more accurately reproduces the regression parameters assumed in the simulation than negative binomial or standard PLN regression. The HQRPLN estimates for contaminated data are competitive with those of classical methods for robust regression using a negative binomial density and M-estimation (Aeberhard et al 2014;Chambers et al 2014), and also with classical methods for median regression for count data (Machado and Santos Silva, 2005). It is also shown that HQRPLN accurately identifies the contaminated observations.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…It is shown that the hierarchical median regression via a Poisson log-normal representation (HQRPLN) more accurately reproduces the regression parameters assumed in the simulation than negative binomial or standard PLN regression. The HQRPLN estimates for contaminated data are competitive with those of classical methods for robust regression using a negative binomial density and M-estimation (Aeberhard et al 2014;Chambers et al 2014), and also with classical methods for median regression for count data (Machado and Santos Silva, 2005). It is also shown that HQRPLN accurately identifies the contaminated observations.…”
Section: Introductionmentioning
confidence: 86%
“…Table 1 contains the resulting regression parameter estimates. It can be seen that negative binomial regression is most vitiated by response outliers, this distortion increasing with C. The Chambers et al (2014) estimates are more robust than negative binomial regression, but not as robust as the Aeberhard et al (2014) estimates or the HQRPLN estimates. Standard Poisson log-normal regression is more robust than the negative binomial regression and the Chambers et al (2014) estimates, but outperformed by the HQRPLN method.…”
Section: Simulated Data Examplementioning
confidence: 94%
See 3 more Smart Citations